Mathematics Education and Language Diversity The 21st ICMI Study - Barwell, Richard; Clarkson, Philip; Halai, Anjum; Kazima, Mercy; Moschkovich, Judit; Planas, Núria; Setati-Phakeng, Mamokgethi; Valero, Paola; Villavicencio Ubillús, Martha (New ICMI Study Series, 2016)
XV, 321 p. 57 illus., 46 illus. in color.